Salmonella sp. Antibody detection in expectant with an early diagnosis of Hyperemesis gravidarum using slide widal test - Dzikra Arwie; Arfiani Nur; Subakir Salnus (Journal of Global Research in Public Health, 2020)
Typhoid fever is a global problem especially in countries with poor hygiene. The main etiologies in Indonesia are S. Typhi, S. enterica, Serovar enterica, and S. Paratyphi A. Pregnant women are very sensitive to infection from various microorganisms, physiologically the immune system in pregnant women decreases, possibly as a result of the tolerance of the mother's immune system to the baby, which is a semi-allogenic tissue. The aim of this research was to detect antibodies to Salmonella sp. in pregnant women with an early diagnosis of Hyperemesis gravidarum using the slide method widal test. Based on the results of research on salmonella sp antibody detection in pregnant women with an early diagnosis of hyperemesis gravidarum using the slide method widal test, there were 80% of salmonella sp. in pregnant women with an early diagnosis of hyperemesis gravidarum. 16 positive samples from 20 total samples, 20% of samples are positive for O series antigens, 40% of samples are positive for O and H series antigens, and 20% of samples are positive for H series antigens.